FEATURES OF CONSTRUCTION OF IMAGE OF MODERN ORGANIZATIONS - G. Kokldanova; E. Lubyanitskaya; A. Nevenchenkova; E. Saliy (Вестник университета)
The article deals with the concept of image and business reputation, proves the necessity of creating and maintaining of a positive image in modern organizations, including state structures. There demonstrated the research of the different ways and channels of communication used in creating the image of socially responsible company by means of social advertising. The article regards the role and the place of communication in building and maintaining the image of the organization.